COMBINATION OF PSYCHOEDUCATION AND VIDEOTHERAPY TO IMPROVE KNOWLEDGE AND ANTI-BULLYING BEHAVIOR IN CLASS V-B STUDENTS MI MA'ARIF NU BANTERAN: CASE REPORT - Yurice Kusuma Putri; Asep Iskandar; Wahyudi Mulyaningrat (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Introduction: Bullying is a form of negative behavior that is repeated and has a negative purpose. Bullying behavior generally leads directly from one child to another due to an imbalance of power. Environmental factors are divided into school and peer factors called conformity. Conformity is a social peer influence that is known as the first phase to group up and have many friends. Purpose: This case study aims to determine changes in knowledge and bullying behavior after providing psychoeducation and videotheraphy to fifth grade elementary school children. Methods: Case study method with the application of Evidence Based Practice (EBP) in a community of school children totaling 23 students. Implementation of EBP with psychoeducation and videotheraphy on 23 students of class V B MI Ma'arif NU Banteran. Implementation was carried out for 5 sessions (3 psychoeducation sessions, 2 videotherapy sessions). Nursing evaluation begins by distributing pre-test questionnaires to students and then students are asked to fill out post-test questionnaires. Discussion: There was a significant increase in knowledge in the good category from 39.1% to 73.9 and changes in bullying behavior which originally had 7 students in the very high category reduced to 5 students. The increase in knowledge after the intervention occurred in all elements contained in the questionnaire including the definition of bullying, characteristics of bullying, characteristics of bullying perpetrators and victims, types and forms of bullying, factors that influence bullying, and the impact of bullying. Conclusion: There is an increase in knowledge and a decrease in attitudes towards bullying behavior.